Provision of spaces and space quality in housing area towards quality of life: case study of Taman Melati Mastika, Gombak - Abdul Malek, Muhammad Faiz; Wan Hashim, Wan Mohamad Saifuddin; Abu Bakar, Aniza; Abdul Malek, Nurhayati; Othman, Rosniza; Sanusi, Aliyah Nur Zafirah; Mohit, Mohammad Abdul (2014)

(untitled)
Every successful housing space is fix upon its user satisfaction living in that space itself. The quality of house and the spaces within the unit can be said as the most compelling factors in scaling the user satisfaction in dwelling in the residential area that can lead to a better quality of life. Limitation of space following high land cost that affect the indoor and outdoor spaces needs to be studied as it affects the residents’ satisfaction. Hence, this study concentrates on spaces within a housing area and their quality, as well as the opinion of the residents and their level of satisfaction and space utilization.The focus of the study is on double-storey terraced houses because it is among the most common and dominant form of housing in Malaysia. The techniques employed in collecting data are observation and survey questionnaire with the respondent rate of 25.2%. This study provides an insight on the types of outdoor spaces (front yard-front lane and backyard-back lane) and their elements and utilization, indoor spaces utilization, and quality of housing spaces toward users’ quality of life in Taman Melati Mastika, Kuala Lumpur. The result of this study suggests that the residents are satisfied with the existing spaces within their compound and adjacent to it, and this lead towards the overall satisfaction living in the area. It can also be said that quality spaces and good utilization of housing spaces can lead towards a better quality of life in the terrace housing area.